Determination of Subgrade Reaction Coefficients and Spring Stiffnesses for a Combined Pile Raft Foundation (CPRF) by Means of a Cluster Analysis - Kanizsár Szilárd (Slovak Journal of Civil Engineering, 2021)
An analysis of combined piled raft foundations could be performed by means of a special geotechnical finite element software that utilizes 3D modeling and advanced constitutive models for the soil. However, a foundation is generally included in the structural models in a structural design program. The least advanced part of finite element software that has been developed for structural FEM modeling are the tools used for modeling behaviour. A method is required with which the input parameters of the structural design software that are used for modeling the soil structure interaction as well could be determined so that the results calculated by means of a geo-technical software that approximates realistic soil behaviour the best can be reproduced by structural design software as well. The procedure outlined in this paper by means of a cluster analysis provides a tool for a substantial and innovative improvement in subsoil modeling, to which not enough attention is generally paid in the structural FEM software, thereby resulting in a reduced amount of work associated with the task of inputting data.